Influence of total quality management on job performance of employees / Mohamad Azraei Hazny Abd Hafiz and Syed Hafiz Syed Fairudz - Abd Hafiz, Mohamad Azraei Hazny; Syed Fairudz, Syed Hafiz (Faculty of Administrative Science and Policy Studies, 2012)
In this study, the researchers are focusing on the Influence Of Total Quality Management On Job Performance Of Employees. The purpose of conducting this study is to find out the relationship between the total involvement and the job performance of employees, to find out the relationship between the customer orientation and the job performance of employees, to find out the relationship between continuous improvement and the job performance of employees, and to find out the relationship between awareness of TQM and the job performance of employees.This research were conducted and to examine whether there is any significance relationship between Total Involvement, Customer Orientation, Continuous Improvements and Awareness of TQM on the job performance of employees. This research is also giving suggestion and recommendation in imlementing the elements of TQM sucessfully. For this study, the researchers used Convenience Sampling as sampling technique. In this study, about 80 respondents are involved and the questionnaire are distributed in National Registration Department of Malaysia, Malacca. These 80 respondents represented on behalf of 100 employees from all department in National Registration Department of Malaysia, Malacca. The researchers used several methods like descriptive analysis, realibility analysis, spearman correlation, and multiple regression. Based on the findings, all 4(four) factors; Total Involvement, Customer Orientation, Continuous Improvements and Awareness of TQM indicate that there are positive relationships with improvements in Job Performanc of employes. Based on the multiple regressions, it shows that Customer Orientation and Awareness of TQM is the most influential factors that contribute to improvements in the job performance of employees which in this case is the public servants at National Registration Department, Malacca.